Світловипромінювальні структури на основі трихінолінату алюмінію (Alq3), модифіковані нанорозмірними плівками похідного піразоліну та йодиду міді - Возняк, Леся Юріївна (Національний університет "Львівська політехніка", 2013)
Дисертаційна робота присвячена розробці та дослідженню органічних світловипромінювальних структур на основі трихінолінату алюмінію (Alq3), модифікованих нанорозмірними плівками похідного піразоліну (HPhP) та йодиду міді (СuI). Розроблені органічні світловипромінювальні структури системи ITO/CuI/Alq3/PEGDE/Al, ITO/HPhP/Alq3/PEGDE/Al з довжиною хвилі випромінювання 530 нм. Показано, що використання нанорозмірних плівок CuI приводить до збільшення яскравості до 4500кд/м2 та зменшення порогової напруги свічення до 4,8 В. Показано, що використання нанорозмірних плівок HPhP як дірково-транспортного шару в структурі ITO/HPhP/Alq3/PEGDE/Al збільшує яскравість до 6560 кд/м2 та струмову ефективність до 9,75 кд/А та сприяє сповільненню деградаційних процесів. Розроблено світловипромінювальні структури в синій області спектру випромінювання ITO/CuI/HPhP/Ca/Al з максимумом спектра випромінювання 455 нм, яка забезпечує яскравість 1450 кд/м2 та високу струмову ефективність 10,63 Кд/А. Показано можність використання нанорозмірних плівок поліаніліну (ПАН) як світловипромінювального шару в структурі ІТО/CuI/ПАН/Ca/Al. Диссертационная работа посвящена разработке и исследованию органических светоизлучающих структур на основе трихинолината алюминия (Alq3), модифицированных наноразмерными плёнками производного пиразолину HPhP и йодида меди (СuI). Разработаны органические светоизлучающие структуры системы ITO/CuI/Alq3/PEGDE/Al, ITO/HPhP/Alq3/PEGDE/Al с длиной волны излучения 530 нм. Показано, что использование наноразмерных плёнок CuI приводит к увеличению яркости до 4500 кд/м2 и уменьшение порогового напряжения свечения до 4,8 В. Показано, что использование наноразмерных плёнок HPhP как дырочной-транспортного слоя в структуре ITO/HPhP/Alq3/PEGDE/Al увеличивает яркость до 6560 кд/м2 и токовую эффективность до 9,75 кд/А и способствует замедлению деградационных процессов. Разработано светоизлучающие структуры в синей области спектра ITO/CuI/HPhP /Ca/Al с максимумом спектра излучения 455 нм, которая обеспечивает яркость более 1450 кд/м2 и токовую эффективность 10,63 кд/А. Показано возможность использования наноразмерных пленок полианилина (ПАН) как светоизлучающие слоя в структуре ІТО/CuI/ПАН/ Ca/Al. The dissertation is devoted to development of organic light emitting structures based on Alq3 with additional hole-injection layer copper iodide (CuI) and hole-transport layer pyrazoline derivatives 2,6-di-tert.-butyl-4-(2,5-diphenyl-3,4-dihydro-2H-pyrazol-3-yl) -phenol (HPhP). It was fabricated organic light-emitting structures ITO/CuI/Alq3/PEGDE/Al, ITO/HPhP/Alq3/PEGDE/Al with green emission at 530 nm by means of vacuum deposition technique. The influence of hole injection layer CuI on the light-emitting properties of ITO/CuI/Alq3/PEGDE/Al based on current –voltage and brightness-voltage characteristics was investigated and it was shown that inserting of CuI injection layer increase brightness up to 4500 cd/m2 and decrease turn-on voltage to 4.8 V. The FTIR spectroscopy of initial powder HPhP and films based on its was used to identify the molecule structure of HPhP after film formation (vacuum deposition). From impedance and current density–voltage measurements it was found that the charge transfer mechanism in the ITO/HPhP/Al structure is characteristic for space charge limited current (SCLC). ITO/HPhP/Alq3/PEGDE/Al device with HPhP films as HTL has turn-on voltages Von = 6.4 V, and exhibit high current efficiency values (9.75 cd/A) and brightness of 6560 cd/m2 (at 14.38 V). Comparing of time dependence of electroluminescent intensity during continuous operation of two types of devices (with and without hindered phenol), we conclude that presence of hindered phenol in HTL leads to the delay of degradation processes in OLED. Presence of hindered phenol in HTL leads to the delay of degradation processes in organic light-emitting structure by formation of stable radicals after oxidation of HPhP. We performed the comparative analysis of luminescence time decay in two types of electroluminescent devices with HTL from pyrazolines derivative with hindered phenol and without it. The two fabricated encapsulated OLEDs (ITO/HPhP/Alq3/PEGDE/Al and ITO/PhP/Alq3/PEGDE/Al) were kept exposed to air for 24 hours and the change of EL intensity in time was monitored during the continuous operation. As was expected, during continuous operation decreasing of initial intensity has been observed due to degradation of OLEDs under applied electric field and formation of dark spots. It should be noted here that during the first 5 minute of work ITO/HPhP/Alq3/PEGDE/Al structure demonstrated a less decrease of initial EL intensity, as compared with ITO/PhP/Alq3/PEGDE/Al structure. After the first 5 min, the behavior of EL decay for both OLEDs was the same. Developed structure ITO/CuI/HPhP/Ca:Al characterized by bright blue emission with a peak wavelength at 445 nm and exhibits brightness 1450 cd/m2 and current efficiency 10.63 cd/A. Also we have observed an electroluminescence of the structure ITO/CuI/PANi/Ca:Al with PANi as emitting layer formed by means of vacuum deposition. Electroluminescent structure based on PAN as emitting layer formed by vacuum deposition exhibits brightness of 280 cd/m2, which is significantly higher than value obtained in previous work.
Светоизлучающие структуры на основе трихинолинату алюминия (Alq3), модифицированные наноразмерными пленками производного пиразолину и йодида меди
Organic light-emitting structures based on organic semiconductor tris(8-hydroxyquinolinato) aluminum (Alq3) with additional layers pyrazoline derivatives and copper iodide
Keywords: органічна світловипромінювальна структура; електролюмінесценція; йодид міді; трихінолінат алюмінію; піразолін; органическая светоизлучающая структура; электролюминесценция; йодид меди; трихинолинат алюминия; пиразолин; organic light-emitting structure; electroluminescence; tris(8-hydroxyquinolinato) aluminum; copper iodide; pyrazoline